2011
DOI: 10.1097/mpg.0b013e3181f57177
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Inflammatory Bowel Disease and Imaging‐related Radiation: Are We Increasing the Likelihood of Malignancy?

Abstract: Although all doses of ionizing radiation have some malignancy-inducing potential, a small but important percentage of children with IBD are exposed to particularly high doses of ionizing radiation from diagnostic tests and procedures. Physicians caring for such patients must seek to limit radiation exposure whenever possible to lessen the lifetime risk of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Therefore, patients with IBD are frequently exposed to diagnostic radiation. Previous studies have shown that a substantial proportion of patients with IBD, especially patients with Crohn's disease (CD), were exposed to significantly harmful amounts of diagnostic radiation, mainly as a result of computed tomography (CT) examination [1][2][3][4][5][6][7]. Recently, we also demonstrated that 34.7 % of patients with CD were exposed to potentially harmful levels of ionizing radiation arising from diagnostic radiography, and abdominopelvic CT (APCT) accounted for 81.6 % of total effective radiation dose of all imaging studies [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, patients with IBD are frequently exposed to diagnostic radiation. Previous studies have shown that a substantial proportion of patients with IBD, especially patients with Crohn's disease (CD), were exposed to significantly harmful amounts of diagnostic radiation, mainly as a result of computed tomography (CT) examination [1][2][3][4][5][6][7]. Recently, we also demonstrated that 34.7 % of patients with CD were exposed to potentially harmful levels of ionizing radiation arising from diagnostic radiography, and abdominopelvic CT (APCT) accounted for 81.6 % of total effective radiation dose of all imaging studies [8].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on radiation exposure of IBD patients have also found that CT contributed the majority of the total effective dose administered to IBD patients 1013,24. Our recent study showed that intestinal complications such as intestinal fistulas, stricture, and abscesses were less frequent in intestinal BD than in CD and that small bowel involvement was uncommon in intestinal BD 25.…”
Section: Discussionmentioning
confidence: 89%
“…Approximately 5.8% of children and 7.1%13% of adults with IBD had an estimated CED > 50 mSv [5153] . Children and adults with CD, history of prior surgery, and prednisone use are more likely to have increased radiation exposure [51,52] . Adults with IBD are also at risk for increased radiation exposure within the first year after diagnosis [52] .…”
Section: Ionizing Radiationmentioning
confidence: 99%
“…A recent study demonstrated multiple CT scans in childhood with cumulative radia tion exposure of 50 mSv tripled the relative risk of leukemia and brain cancer [50] . Retrospective data among the pediatric IBD population suggests the average cumulative effective dose (CED) over an extended period of time was 20.5 mSv among children with CD and 11.7 mSv with UC [51] . Retrospective data among adults with IBD estimates CED was 20.1 mSv for patients with CD and 15.1 mSv with UC [52] .…”
Section: Ionizing Radiationmentioning
confidence: 99%